Antimicrobial Activity of Essential Oils of some Abies (Fir) Species from Turkey - Bagci, Eyup; Digrak, Metin (Wiley-Blackwell, 1996)
The antimicrobial activity of essential oils isolated from nine Abies species (Abies koreana Wills, A. alba Mill., A pinsapo Boiss.. A. concolor (Gord. et Glend.) Lindl. ex Hildebr., A. firma Sieb. et Zucc. (all of these exotic for Turkey), A. nordmanniana (Stev.) Spach. subsp nordmanniana which are plantation forms; and A. cilicica (Ant. et Kotschy.) Carr. subsp. cilicica, A. cilicica (Ant. et Kotschy.) Cam. subsp. isaurica Coode et Cullen, A. nordmanniana (Stev.) Spach. subsp. bornmuelleriana Mattf. which are natural forms against nine bacteria (Escherichia coli, Bacillus megaterium, B. cereus, B. subtilis, B. brevis, Pseudomom aeruginosa, Listeria monocytogenes, Klebsiella pneumoniae, Enterobacter aerogenes, Staphylococcus aureus and two yeasts (Saccharomyces cerevisiae and Candida albicans) have been investigated using a disc diffusion method. The results suggested that the essential oils tested for antimicrobial activity can be classified into three groups according to the strength of their antimicrobial activities. The first group of essential oils of A. pinsapo and A. concolor does not have any antimicrobial activity, the second group of essential oils, isolated from A. alba and A. firma, had a modest activity. The third group, which consisted of A. koreana, A. cilicica subsp. cilicica, A. cilicica subsp. isaurico, A. nordmanniana subsp. nordmanniana and A. nordmanniana subsp. bornmuelleriana essential oils, had the highest antimicrobial activity against the bacteria and yeast species tested. Surprisingly, it was found that most of the essential oils used in this study had little effect on the growth of E. coli. The essential oils of the nine Abies species tested for antimicrobial activity were more active against yeast species than against bacteria, and the antimicrobial activity of essential oils was variable, depending on the bacterial strains and the source of the essential oil.
Keywords: Abies alba Mill.; A. koreana Wills.; A. firma Sieb. et Zucc.; A. concolor (Gord. et Glend.) Lindl. ex Hildebr.; A. pinsapo Boiss; A. cilicica (Ant. et Kotschy.) Carr. subsp cilicica; A. cilicica (Ant. et Kotschy.) Carr. subsp isaurica Coode et Cullen; A. nordmanniana (Stev.) Spach. subsp bornmuelleriana Mattf.; A. nordmanniana (Stev.) Spach. subsp nordmanniana; essential oils; antimicrobial activity; bacteria; yeasts